Pengaruh POS terhadap Service Oriented-Organizational Citizenship Behavior yang Dimediasi Oleh OC pada Karyawan Bidang Pelayanan BPJS Ketenagakerjaan Se-Jawa Timur: (The Effect of POS on Service Oriented-Organizational Citizenship Behavior Mediated by OC on Employees of BPJS Ketenagakerjaan in East Java) - Shafira Khairunnisa; Praptini Yulianti (e-Journal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to determine the effect of POS on SOCB with the mediating role of OC. This study uses a quantitative approach with the analytical technique used is partial least square with 108 respondents in the service sector employees throughout East Java at BPJS Ketenagakerjaan. The dependent variable used is the service-oriented organizational citizenship behavior, the independent variable is the POS, and the mediating variable is the POS. The results of the study indicate that perceived organizational support can affect the behavior of service-oriented organizational citizenship of service employees with positive and significant results. Perceived organizational support also shows a positive and significant impact on service-oriented organizational citizenship behavior mediated by OC.